Evaluation of the Water Quality of Two Different Bottled Waters Supplied Onboard Offshore Service Boat - Otuaro Ebierin Akpoebidimiyen and Igoma, Emughiphel Nelson (International Journal of Research Publication and Reviews, 2025)
The nature of water supplied onboard vessels denotes the fastidious problem with the supply of clean drinkable water. Intendedly, the provision of water to drink, for the preparation of food, for washing together with water to bathe can possibly be polluted at different stages, either direct from the source of the water or during loading. Based on this conspicuous reason of pollution or contaminants in drinking water, the evaluation of the water quality of two different bottled waters supplied onboard offshore service boats has been done. The two bottled waters were taken from two separate companies that supplied water to the Oil Service Tug boat for a water quality test. One of the bottled water was labelled – S and the other bottled water labelled – D according to the first initials of the two companies that supply the water respectively. These dissimilar samples of S and D were stored in a cool flask of about 250ml of ice block at less than 100C and then taken to the laboratory for physical, chemical coupled with biological evaluations. The test for the colour and odour shows colourless and unobjectionable and the other test results are pH is 6.6, turbidity - TDS – 2mg/L, electrical conductivity – 4us/cm, total alkalinity -20.8mg/L, chloride -60mg/L, total hardness – 0.1mg/L, sulphate -<1, nitrate – 0.09, total iron -<0.06 , lead -<0.01 and coliform is 0.00 cfu/100ml for Sample S and Sample D results are pH – 7.2, turbidity - <0.1, TDS – 23mg/L, electrical conductivity – 46.6us/cm, total alkalinity -62.2mg/L, chloride -75mg/L, total hardness – 0.2mg/L, sulphate -<1, nitrate – 0.04, total iron - <0.06, lead -<0.01 and coliform is 0.00 cfu/100ml respectively. These values were compared to WHO standard water values and they are in compliance with it, showing that the water is good for drinking. Also, the water is devoid of bacteria, has no suspended solid particles, and it is hygienically good for consumption.
Keywords: Evaluation; Water Quality; Different Bottled Water; Supply Onboard; Offshore Service Boat.